A systematic review and meta-analysis of computed tomography in the diagnosis of pediatric foreign body aspiration. (February 2023) - Azzi, Jayson Lee; Seo, Chanhee; McInnis, Graham; Urichuk, Matthew; Rabbani, Rasheda; Rozovsky, Katya; Leitao, Darren J.
Abstract: Introduction: Rigid bronchoscopy remains the gold standard for the diagnosis of foreign body aspiration (FBA) despite high rates of negative bronchoscopies. The use of computed tomography (CT) imaging in the assessment of FBA has recently emerged and could help obviate unnecessary bronchoscopy in these patients. The aim of this study is to assess the diagnostic accuracy of CT in the diagnosis of pediatric FBA. Methods: A systematic literature review was conducted to identify studies reporting the use of CT imaging in suspected pediatric FBA. The search included published articles in Ovid MEDLINE, Ovid EMBASE, PubMed MEDLINE and Web of Science. The search strategy included all articles from inception of the database to January 2021. Manuscripts were reviewed and graded for quality using the QUADAS-2 tool. Subgroup analyses based on the use of virtual bronchoscopy (VB) and sedation was conducted. A meta-analysis evaluating the use of VB in the diagnosis of FBA was also conducted. Results: Sixteen manuscripts met all inclusion criteria. In total, 2056 pediatric patients ranging from 0.3 to 15 years underwent CT for suspected FBA. The sensitivity and specificity of CT were 98.8% and 96.6%, respectively. VB was used in 71.4% (1391/1948) of patients while sedation during CT was required in 70.2% (1263/1800) of patients. Radiation dosing ranged from 0.04 to 2 mSv, 0.99–59.1 mGy-cm and 0.03–16.99 mGy. Conclusion: CT can accurately diagnose pediatric FBA and can help decrease the rate of unnecessary bronchoscopies with an acceptable dose of radiation. Highlights: CT is accurate in diagnosing pediatric FBA. CT can be safely used to diagnose pediatric FBA without excessive radiation. CT can help decrease the rate of negative bronchoscopies in pediatric FBA.